Elite sports policy and coaching at the coalface - Liston, K.; Gregg, R.; Lowther, J. (International Journal of Sport Policy and Politics, 2013)
This article marks an important watershed in the investigation of elite sport development in the `Atlantic Isles`. It outlines some features of the emergence and development of international elite sports policy and its idiosyncratic diffusion to Northern Ireland (NI) specifically. Drawing on the SPLISS framework and the need for empirical work within Pillar 7 (coaching provision and coaching development), there is also an examination of elite coaches` perceptions of the policy factors influencing international sporting success. This goes some way towards redressing the dearth of knowledge about the complex social and political realities in which elite coaches ply their trade. A `mixed methods` approach was employed, which incorporated secondary analysis of government and sports policy documents, the historical charting of the elite sports policy field in NI, the completion of an internationally validated survey and also semi-structured interviews with eight high-performance coaches (seven males and one female) who ranged in age from 38 to 59 years. The study demonstrates some of the unique challenges for the dual positioning of NI within Irish and British sports governance arenas. There, the resultant fractured elite sports policy landscape has constrained coaches` attempts to deliver upon performance targets. There was also less than convincing evidence of a `high-performance` oriented sport culture. The article concludes by bridging the gap between sports policy and social policy in NI and, in so doing, offers some possibilities for developing a more integrated research agenda.